Argumentación y periodismo de opinión, el caso de maría Jimena Duzán (2011)
This project aimed at general level interpreted from the theory of argumentation, the most frequent uses of it in opinion journalism, from the columns of the Colombian journalist María Jimena Duzan, published in the magazine Semana, between May 28 and 15 October 2011. The project also was delimited from three specific objectives that identified uses of language, theory of truth, objectivity and subjectivity, types of arguments and fallacies in the columns of the journalist, to contrast the theory of argumentation with the columns of Maria Jimena Duzan view and relate the theory of argumentation opinion journalism and contributions offered by the argument to journalism. The research method used was qualitative. Similarly, the project was kind of hermeneutic.